Peran Komunikasi Organisasi Dalam Pendidikan Atau Pembelajaran Pada MAS Mu’alimin UNIVA Medan - Nur, Agung Muhammad; Siregar, Ahmad Rinaldi; Nurarfiansyah, Lucky Tirta; Maulida, Sifa; Widyana, Tasya; Syahputra, Muhammad Rizki (LPPPI Publishing, 2024)
This research was conducted to answer the role of organizational communication in education or learning at MAS Muallimin Univa Medan. The research conducted was qualitative research with data collection techniques through interviews. Organizational communication is the flow of information, exchange of information, and transfer of meaning in an organization. Based on the results of research obtained from interviews with several teachers, it can be concluded that the teaching and learning process carried out by teachers is always an interaction activity between students as learning parties and teachers as teaching parties. This process itself is a chain that connects between teachers and students so as to create communication that has a purpose, namely learning objectives. Teachers must create an interactive classroom atmosphere where students can actively participate in the teaching and learning process.